Reduksi Sampah Organik dengan Vermicomposting: (Studi Kasus Pasar Panjang Jalan Sorumba, Kota Kendari, Sulawesi Tenggara) - Maulana Baka, Rezki; Ndibale, Wa; Eka Pratiwi, Yunita (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
Organic waste generation is the remains of materials originating from living things, both plants and animals, resulting from human activities or natural processes and can be decomposed biologically. Vermicomposting is the process of decomposing organic waste with the help of earthworms which produces a better end product called Vermicast. This study evaluated the generation of organic vegetable and fruit waste in Pasar Panjang, the quality of compost from vermicomposting with and without finished compost and the reduction of organic waste. Samples were taken from 4 out of 57 stalls using the SNI 19 3964 1994 sampling method. The results of the analysis showed that the generation of organic vegetable and fruit waste reached 10,463 kg per stall per day with a volume of 13,973 liters per stall per day. The composition of the waste consisted of 75.345% vegetable waste and 24.655% fruit waste, with a density of 0.751 kg/L. The quality of compost produced from the vermicomposting method with and without the addition of finished compost shows the results of the parameters: color, odor, and particle size, temperature, water content of C-organic and N-organic meet the standards, SNI while pH and C/N ratio do not meet the SNI standards. In terms of effectiveness, the use of vermicomposting without the addition of finished compost shows a higher level of reduction in organic waste generation, which is 53.3%, compared to the use of finished compost which only reaches 36.8%.